Aprocitentan: a new emerging prospect in the pharmacotherapy of hypertension - Lina Naseralallah; Somaya Koraysh (Blood Pressure)
Background Resistant hypertension (RH) is linked to higher risks of cardiovascular events and there remains an unmet therapeutic need driven by pathophysiologic pathways unaddressed by guideline-recommended therapy. Whilst spironolactone is considered the preferred fourth-line therapy, its broad application is limited by its safety profile. Aprocitentan is a novel dual endothelin (ET) A and B receptors antagonist that has been recently approved by the FDA.Objective This review aims to summarise the available evidence on the discovery, pharmacokinetic, pharmacodynamic, efficacy, and safety of aprocitentan in the pharmacotherapy of RH.Methods We searched PubMed, Embase, and International Pharmaceutical Abstracts to identify relevant papers on aprocitentan use. Clinical trial registries were also searched.Results Aprocitentan targets the ET pathway which remains unopposed by contemporary alternative therapies for RH. It differs from other ET receptor antagonists in its pharmacological profile, as it is eliminated independently of CYP450 or BCRP, making it less likely to cause drug–drug interactions. Current evidence demonstrates that compared to placebo, aprocitentan significantly reduces blood pressure (BP) as measured via unattended automated office BP and 24-hour ambulatory BP. The most frequently reported adverse effects were fluid retention/edema and anaemia.Conclusion Aprocitentan is a novel therapy for the management of RH that significantly reduces BP when compared to placebo. It delivers exciting prospects for future therapeutic options in the setting of RH and expands insights into its pathophysiology. However there is lack of data in relation to broader cardiovascular and renal protection, as well as its long-term safety profile.